مقاربات المجتمع المدني من العقد الاجتماعي حتى يورغن هابرماس - رضا، بشرى حسن (د محمد أمين الضناوي, 2024)
هدفت هذه الدراسة الموسومة بـ "مقاربات المجتمع المدني من العقد الاجتماعي حتى "يورغن هابرماس" إلى استعراض المقاربات النظرية التي واكبت بداية تبلور هذا المفهوم. وقد خلصت إلى مجموعة من النتائج، تجلت في تبلور نظرية التعاقد الاجتماعي Social Contracting Theory كنظرية معادية لنظرية الحق الإلهي للملوك في مجال الحكم. ورأى "آدم فرغسون" (Adam Ferguson)، في المجتمع المدني أداة للتقليل من تمركز السلطة والحد من الاستبداد ليسند توماس بين (Thomas Bean) (1791) إلى المجتمع المدني دورا أكبر من دور الدولة ليجعله العنصر الذي يتولى الشؤون العامة لكي يتقلص دور الدولة في المجتمع، فيصبح المجتمع المدني أداة للتقليل من تمركز السلطة والحد من الاستبداد. أما هيغل (Hegel) الألماني الذي عاصر مدة ضعف الدولة الألمانية، فقد رأى عكس ما جاء به آدم فرغسون، أي على الدولة أن تكون قوية وفوق المجتمع المدني، لكي تحقق تقدم المجتمع الألماني وتضمن التعددية. ورأت النظرية الماركسية أن المجتمعات البشرية تتطور من خلال الصراع الطبقي ضمن نمط الإنتاج الرأسمالي، وهذا الصراع يتجلى بين الطبقات البرجوازية الحاكمة، والمالكة لوسائل الإنتاج من جهة والطبقات العاملة المعروفة باسم البروليتاريا وهي الطبقات التي تبيع قوة عملها من خلال عائد الأجور؛ فالمجتمع المدني هو قاعدة مادية مؤسسة للدولة. وتصور أنطونيو غرامشي (Antonio Gramsci) المجتمع المدني كمجال اجتماعي، فيه تنشأ وتدور بين الأفراد والجماعات الصراعات والخلافات ذات الطابع الإيديولوجي. وتشكل المفاهيم المختلفة للمجتمع المدني، في مفهوم ماكس فيبر أساس النقاشات الجارية حول أدوار الدول والأسواق المناسبة. ويعد المجتمع المدني عامة مجالا إيجابيا يساعدنا على التمتع بالسلطة والاستقلالية. وطور يورغن هابرماس مفهوم الخاص بالفعل التواصلي، وهو العملية التي يقوم من خلالها الأشخاص بتكوين هوياتهم، وفقا لقاعدة تعمل من خلالها الأفعال التواصلية على نقل المعرفة الثقافية، وتجديدها في سياق عملية تحقيق التفاهم المتبادل؛ ثم تقوم بتنسيق العمل نحو التكامل الاجتماعي والتضامن. This study, titled “Civil Society Approaches from the Social Contract to Jürgen Habermas”, aimed to review the theoretical approaches that accompanied the beginning of the crystallization of this concept. It reached a set of results, manifested in the crystallization of the theory of social contracting theory as a theory hostile to the theory of the divine right of kings in the field of government. Adam Ferguson saw civil society as a tool to reduce the concentration of power and limit tyranny, so Thomas Bean (1791) assigned civil society a greater role than the role of the state to make it the element that handles public affairs in order to reduce the role of the state in society, where civil society becomes a tool to reduce the concentration of power and reduce tyranny. Hegel, a German who lived through the weakness of the German state, saw the opposite of Adam Ferguson’s, namely that the state must be strong and above civil society in order to achieve the progress of German society and ensure pluralism. Marxist theory held that human societies develop through class struggle within the capitalist mode of production, manifested between the bourgeois classes ruling and owning the means of production on the one hand and the working classes known as the proletariat, classes that sell their labor power through wage revenue; civil society is the material base of the state. Antonio Gramsci envisions civil society as a social sphere, in which ideological conflicts and disagreements arise between individuals and groups. In Max Weber’s concept, different concepts of civil society form the basis of ongoing debates about the roles of states and appropriate markets. Civil society is generally a positive field that helps us enjoy power and autonomy. Jürgen Habermas developed the concept of communicative action, the process by which people form their identities, according to a rule by which actions work communicative on the transfer and renewal of cultural knowledge, in the context of the process of achieving mutual understanding; then coordinates action towards social integration and solidarity.
Keywords: علم الاجتماع -- نظرية التعاقد الاجتماعي -- هابرماس، يورغن